ANALISIS K3 BERDASARKAN JSA PADA PENGELASAN TANGKI MINYAK PERTAMINA DI SP OGAN FIELD EP ASSET 2 - Putra, Toni Satria; Halawa, Analiser; Tambun, Bungaran (Jurnal Sains dan Teknologi ISTP, 2024)
The purpose of this study is to know the application of occupational safety health (K3), to know the Job Safety Analysis (JSA) as an effort to prevent accidents due to welding work at the bottom of the oil collection tank. application of the Risk Control Hierarchy According to Iso 45001 in the process of welding the bottom of the oil collection tank. In this study, the survey method was used. Then analyzed descriptively aims to describe the nature of a situation. The results of the research on welding the bottom of the pertamina oil collection tank at SP OGAN FIELD EP ASSET 2 have been implemented as written in the Standard Operating Procedure (SOP). The application of Job Safety Analysis (JSA) in the tank bottom welding process has been applied by workers by wearing Personal Protective Equipment (PPE). Welding work on the bottom of the oil collection tank has been carried out based on the Risk Control Hierarchy according to Iso 45001, namely, providing training to workers, conducting regular equipment inspections, wearing personal protective equipment and minimizing and even eliminating hazards that can occur when welding work is done.